Reliability and accuracy of cross-sectional radiographic assessment of severe knee osteoarthritis: role of training and experience - Klara, Kristina (J Rheumatol, 2016)
OBJECTIVE: To determine the reliability of radiographic assessment of knee osteoarthritis (OA) by non-clinician readers compared to an experienced radiologist. METHODS: The radiologist trained three non-clinicians to evaluate radiographic characteristics of knee OA. The radiologist and non-clinicians read preoperative films of 36 patients prior to total knee replacement. Intra- and inter-reader reliability was measured using the weighted kappa statistic and intra-class correlation coefficient (ICC). Kappa <0.20 indicated slight agreement, 0.21 – 0.40 fair, 0.41 – 0.60 moderate, 0.61 – 0.80 substantial, and 0.81 – 1.0 almost perfect agreement. RESULTS: Intra-reader reliability among non-clinicians (kappa) ranged from 0.40 to 1.0 for individual radiographic features and 0.72 to 1.0 for Kellgren-Lawrence (K-L) grade. ICCs ranged from 0.89 to 0.98 for the Osteoarthritis Research Society International (OARSI) Summary Score. Inter-reader agreement among non-clinicians ranged from kappa of 0.45 to 0.94 for individual features, and 0.66 to 0.97 for K-L grade. ICCs ranged from 0.87 to 0.96 for the OARSI Summary Score. Inter-reader reliability between non-clinicians and the radiologist ranged from kappa of 0.56 to 0.85 for KL grade. ICCs ranged from 0.79 to 0.88 for the OARSI Summary Score. CONCLUSION: Intra- and inter-rater agreement was variable for individual radiograph features but substantial for summary KL grade and OARSI Summary Score. Investigators face trade-offs between cost and reader experience. These data suggest that in settings where costs are constrained, trained non-clinicians may be suitable readers of radiographic knee OA, particularly if a summary score (K-L grade or OARSI Score) is used to capture radiographic severity.